THE DEVELOPMENT OF SOCIAL MEDIA AMONG TEENAGERS WHICH POTENTIALLY VIOLATES THE LAW - hartanto, hartanto; Anwar Hidayatulloh, Bagus; Yosa Pratikta, Fairus (fakultas hukum universitas PGRI Semarang, 2024)
Social media platform very a lot, writer interested research about TikTok as a platform that is quite trending with utilise take niche market, namely duration videos short , and Indonesia is ranked as the second most TikTok user in the world. Social media is quite influential in the social development of society, but the rules on each platform are often still normative and not applied regularly, such as the features for reporting violations of community rules. The positive side of social media is that it triggers people's creativity (especially teenagers), but it cannot be denied that there are also negative sides, ranging from consumerism to ethical degradation and can even develop into criminal acts, even though there are many positive legal instruments that regulate it, one of which is the information law and electronic transactions, and juvenile criminal justice system laws. In closing, the author believes that the government's role is not limited to creating regulations, but must actively monitor the development of social media in collaboration with electronic organizers so that the negative impact on the younger generation can be controlled.